Young People and Mental Health in the Risk Society: The Impact of Labor Market Insecurity - Mojić, Dušan C.; Jeličić, Aleksandra Č. (Sociološki pregled, 2019)
The paper analyses the impact of labor market insecurity on mental health of young people in contemporary societies. This insecurity has been viewed as a part of new risks in the (global) risk society. Difficult transitions to adulthood have been mostly characterized by hardships in transition from education to employment. Relative employment security and “standard” careers of previous generations have been replaced by delayed, fragmented and diversified education-to-work life pathways. Imposed individualization in the circumstances of scarce and unevenly distributed resources can often affect the mental health of young people. Keywords: youth, labor market, risk society, mental health.